Spectroscopic review of chelating agents and their influence on the bioavailability of Fe, Zn and Ca in Fijian foods. Issue 7 (8th August 2020) - Singh, Poonam; Prasad, Surendra
Abstract: The spectroscopic review of few chelating agents to assess their influence on minerals bioavailability is presented and methods used for the determination of phytic acid (PA) and tannin (TA) in foods have veen reviewed. Phytate (PA) is available in cereals and legumes while TA is present in legumes, some cereals, fruits and beverages. As PA and TA are known to influence the functional and nutritional properties of foods so their contents in Fijian foods have been reviewed spectrophotometically and influence of PA and ethylenediaminetetraacetic acid (EDTA) on the bioavailability of minerals (Fe, Zn and Ca) in foods is investigated. The pulses/legumes and green leafy vegetables (GLVs) showed high contents of PA and TA with large variation in their contents. The highest content of PA was found in GLVs i.e., dalo leaves 216.79 followed by spinach 204.55 mg/100 g while TA contents were 1097.01 and 1544.78 mg/100 g, respectively. The molar ratios of PA to individual mineral (Fe, Zn and Ca) have also been determined to show the effect on these minerals' bioavailability. The influence of PA and EDTA on the bioavailability of Fe, Zn and Ca in chickpea, red kidney bean, green gram (whole moong) and brown bread has also been discussed compared.